Strategies to support developing talent - Fuchslocher, J.; Romann, M.; Gulbin, J. (Schweizerische Zeitschrift für Sportmedizin und Sporttraumatologie, 2013)
The high performance unit within the Swiss Federal Institute of Sports Magglingen (SFISM) is chartered with supporting talented athletes via its collective inputs to students, athletes, coaches and national sporting federations. This is achieved by drawing upon the multi-disciplinary expertise of practitioners in the areas of sports medicine, recovery and rehabilitation, training science, sports psychology, nutrition, endurance and power physiology, strength and conditioning, and data management. This critical mass of specialists provides opportunities to collaborate "broadly" across a specific talent theme (e.g. on what basis should we select future sporting talent?), as well as the provision of sufficient content expertise to provide "deeper" knowledge and insights related to these interdisciplinary discussions (e.g. how can we account for biological maturity?). Therefore, this paper presents an example of the "broad" interdisciplinary work undertaken by SFISM to improve talent selection, and the complementary "deep" work used to investigate biological maturation as one component of this process. New and ongoing projects will continue to harness the collective potential of the multidisciplinary experts to better understand the processes of talent identification, selection, and development at the broadest and deepest levels. Our collective ability to support Switzerland`s best and brightest talent will require us to maximise the considerable expertise of the many stakeholders which influence and impact on development.